A new 12, 17-cyclo-labdane diterpenoid from the twigs of Dacrycarpus imbricatus. Issue 14 (18th July 2018) - Yang, Zuofa; Wang, Qiuxiang; Peng, Wei; Zhan, Rui; Chen, Yegao
Abstract: A new 12, 17-cyclo-labdane diterpenoid, podoimbricatin C (1 ), along with 15 known compounds was isolated from the twigs of Dacrycarpus imbricatus . Their structures were elucidated by means of extensive spectroscopic analysis. Compound1 is the second example of the unusual 12, 17-cyclo-labdane diterpenoids. It showed no inhibitory effects against five human tumour lines (HL-60, SMMC-7721, A-549, MCF-7 and SW-480). Abstract :